El rendimiento de la cebolla mejora mediante tácticas de manejo integrado de malezas en el valle medio de Awash, Etiopía - Getahun, Sileshi (2024)
Weeds play a significant role in reducing onion production and productivity in Ethiopia. There is limited information on onion weed management in the hot lowland part of the Country. This study evaluates the effectiveness of integrated weed control tactics in onion crops. The treatments were arranged in a randomized complete block design (RCBD) with three replications. The data collected included different weed species, density, and dry weight of weeds, Additionally, onion yield and yield traits had been taken at maturity. The experimental field was infested by grassy and broad-leaved species of weeds including sedge, the predominant weed species. The result of onion yield and yield traits were significantly (p < 0.05) different among treatments. The three-hand hoeing and Pendimethalin 500 SC + Oxyfluorfen 24 EC supported by one-hand weeding on the 70th day after transplant demonstrated superior weed control efficiency as a result they increased onion bulb yield. Cost-benefit analysis indicated that these two weed management approaches provided the highest cost-benefit ratios (15.84 and 13.25) respectively, and recommended for weed management in onion production. Using pre-emergence pendimethalin followed by timing application of Oxyfluorfen 24 EC and hand hoeing after transplanting can suppress weeds effectively and improve weed control efficiency.